Analysis of Food Buying and Selling with the All You Can Eat System: An Approach from the Perspective of Scholars Sheikh Shalih Al-Fauzan & Sheikh Ibn Utsaimin - Fitria Amania; Yasyifa Rizqi; Hilman Fauzi Lubis hilman; M. Husein Syuhada Tarigan Husein; Manswab Mahsen Abdulrahman (Jurnal Sahabat ISNU SU, 2024)
This study aims to analyze the practice of buying and selling food using the All You Can Eat (AYCE) system from an Islamic legal perspective, specifically according to the views of scholars Sheikh Shalih Al-Fauzan and Sheikh Ibn Uthaymeen. The AYCE system, which offers customers all-you-can-eat food at a fixed price, has become a trend in various restaurants, but has sparked debate regarding its suitability with the principles of Islamic fiqh. This study uses a qualitative approach with a literature review of fatwas and the opinions of the two scholars. The results of the analysis show that both scholars have views that focus on the aspects of fairness and ambiguity in transactions in the AYCE system. Sheikh Shalih Al-Fauzan emphasizes the importance of clarity in transactions and there are no elements that are detrimental to both parties, while Sheikh Ibn Uthaymeen believes that if there is an element of uncertainty in the amount of food consumed, the system could potentially contain elements of gharar (unclearness) which is prohibited in Islam. Therefore, the conclusion is that the practice of AYCE can be considered if it meets the principles of fairness and clarity of transactions according to Islamic law. This research is expected to provide further insight for business actors and the public in understanding the aspects of Islamic law related to modern food buying and selling practices.